Sổ tay 05 nguyên tắc cho công nhân để đảm bảo an toàn thịt lợn tại lò mổ ở Việt Nam - International Livestock Research Institute (International Livestock Research Institute, 2020)
The purpose of this handbook is to support national food safety authorities and food chain stakeholders in promoting good practices among slaughterhouse workers at abattoirs of Vietnam. The target audience are slaughterhouse workers, slaughterhouse owners, national food safety authorities, veterinaries, and policymakers. There are five good practices designed for workers in slaughterhouse mentioned in this handbook. Each key message is accompanied with detailed explanation and real-life pictures for ‘how-to-do’ illustration. We use green bars for pictures of recommended practices, and red bars for pictures of un-recommended ones. Five keys to retailers include: - Key 1: Slaughter on grids and/or tables - Key 2: Be clean - Key 3: Maintain clean condition - Key 4: Be inspected and recognized - Key 5: Be trained This handbook is made possible by the support of the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Research Program on Agriculture for Nutrition and Health (A4NH). The book is an output of the ‘market-based approaches to improving the safety of pork in Vietnam’, or SafePORK project that is led by the International Livestock Research Institute (ILRI) in partnership with the Hanoi University of Public Health (HUPH), the Vietnam National University of Agriculture (VNUA), the National Institute of Animal Science (NIAS) and the University of Sydney.